Systems-wide proteomic analysis in mammalian cells reveals conserved, functional protein turnover - Cambridge, Sidney; Gnad, Florian; Nguyen, Chuong; Lorenzo Bermejo, Justo; Krüger, Marcus; Mann, Matthias (Journal of proteome research, 2011)
The turnover of each protein in the mammalian proteome is a functionally important characteristic. Here, we employed high-resolution mass spectrometry to quantify protein dynamics in nondividing mammalian cells. The ratio of externally supplied versus endogenous amino acids to de novo protein synthesis was about 17:1. Using subsaturating SILAC labeling, we obtained accurate turnover rates of 4106 proteins in HeLa and 3528 proteins in C2C12 cells. Comparison of these human and mouse cell lines revealed a highly significant turnover correlation of protein orthologs and thus high species conservation. Functionally, we observed statistically significant trends for the turnover of phosphoproteins and gene ontology categories that showed extensive covariation between mouse and human. Likewise, the members of some protein complexes, such as the proteasome, have highly similar turnover rates. The high species conservation and the low complex variances thus imply great regulatory fine-tuning of protein turnover.
Gesehen am 27.06.2022